Prenatal marijuana exposure and visual perception in toddlers: Evidence of a sensory processing deficit - Bailey, Beth A.; Osborne, Jahla B. (Frontiers in Pediatrics, 2023)
Background: Research has identified a link between prenatal marijuana exposure and multiple outcomes in children, including cognitive development. Several studies have found specific differences in sensory processing and attention, with visual perception especially impacted in school age children. The current study explored whether this effect is evident at an earlier age, and thus our goal was to investigate the relationship between in-utero marijuana exposure and sensory processing capabilities in toddlers. We hypothesized that in-utero marijuana exposure throughout pregnancy would specifically predict visual sensory hyperactivity in children as young as 15 months of age. Methods: Participants were 225 15-month-old children whose mothers were recruited during pregnancy. Substance exposure was prospectively collected and biochemically verified, with marijuana coded as no exposure, 1st trimester exposure only, or exposure throughout pregnancy. The Infant Toddler Sensory Profile evaluated 5 domains of sensory processing (visual, auditory, tactile, vestibular, oral). Results: Prenatal marijuana exposure throughout pregnancy, but not when limited to the first trimester, predicted a two-fold increased likelihood of scoring in a range indicating high levels of seeking out and potentially over-attending to visual stimulation after controlling for potentially confounding factors including other prenatal exposures. Marijuana exposure was not significantly related to other processing domains. Conclusions: Results indicate that links previously identified between prenatal marijuana exposure and visual function and attention may already be evident at 15 months of age, and also suggest an impact related to continuous/later pregnancy exposure. Our findings, as well as those from previous studies, all suggest visual processing differences for exposed children, differences that may predict emerging issues with visual attention and habituation. As legalization of marijuana continues to increase, further research is clearly needed to examine specific teratologic effects associated with use during pregnancy.